Historie og kulturel erindring i Det Gamle Testamente - Lemche, Niels Peter (Dansk teologisk tidsskrift, 2013)
Resumé It is an established fact that biblical historiography is fundamentallydifferent from modern historical reconstructions. It was neverthe aim to describe the past as it really was. The purpose of historiographywas didactic, and the means had little to do with modern historicalreconstructions. In this way it is preferable to consider biblicalhistoriography to be cultural memory, and it is sharing with memorythe right not to be dependent on historical facts. Rather it represents a“memory” of the past as constructed by an elite group – the few whowere able to write and read. It is possible to reconstruct the “profi le” ofthese intellectuals and their aim: to write a national history, and clearlyfor propagandistic reasons, to support the primacy of Jerusalem over Samaria.Most likely this historiography dates to the Hasmonean period,